Handmade Cranioplasty: An Obsolete Procedure or a Surgery That Is Still Useful?. Issue 4 (June 2020) - Zoli, Matteo; Di Gino, Marco; Cuoci, Andrea; Palandri, Giorgio; Acciarri, Nicola; Mazzatenta, Diego
Abstract : Abstract: Custom made cranioplasty (CM CPL) represents the gold standard for cranial defect reconstruction, allowing an adequate protection of the brain with good cosmetic results. Nevertheless, it is an expensive procedure, requiring time for preparation of the prothesis. Aim of this study is to evaluate whether and in what cases handmade cranioplasty (HM CPL) still represents a valid alternative to CM CPL. Therefore, all consecutive cranioplasties in our center from 2013 to 2019 have been analyzed. Size and location of cranial defect have been considered, as the cause of decompression. Morbidity rate and final outcome have been evaluated. Series includes 143 patients (61% males, mean age: 60 years, SD:16). HM CPL was performed in 59 cases (41.2%) and CM in the remaining 84 (58.8%). HM CPL was preferred for smaller cranial defects (p: 0.22), inferior to 100 cm 2 (p: 0.01) located in fronto-parietal-occipital area (p: 0.01). Furthermore, HM CPL results in the first choice after removal of infiltrative tumors (p: 0.02). Surgical complications consisted in 14 (9%) infections, 8 hematomas (5.6%), and one cranioplasty displacement (0.7%). At follow-up, in 85.3% of cases the CPL is still in place with satisfactory cosmetic and functional outcome (86.5% of HM CPL, 84.5% of CM CPL). HM CPL may still represent an effective and economic alternative procedure, when specific patient selection criteria are respected. This technique requires a long learning learning curve and demanding surgical maneuvers. Our handmade reconstruction technique with some hints to improve the esthetic result is presented. Abstract : Supplemental Digital Content is available in the text